2013
DOI: 10.1063/1.4816444
|View full text |Cite
|
Sign up to set email alerts
|

Defect controlled ultra high ultraviolet photocurrent gain in Cu-doped ZnO nanorod arrays: De-trapping yield

Abstract: Understanding the mechanism behind high photocurrent gain is very important to realize a highly functional material for photodetector devices. Herein, we report a very high ultraviolet photocurrent gain of 2.8 × 105 in hydrothermally grown Cu-doped ZnO nanorod arrays which is two orders of magnitude higher as compared to the undoped sample. Trapping of carriers under dark and de-trapping them under illumination by Cu-related defects is responsible for high gain. The trap state at ∼1.65 eV is attributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…The UV photodetectors used the multiple 1D‐NSs method. Figure (a) and (b) reveal the photocurrent spectra and UV on/off functional switching of the Cu‐doped ZnO and pure ZnO 1D‐NSs . The photocurrent spectra allow sufficient time to show the de‐trapping yield, and this and an X‐ray photoelectron spectroscopy (XPS) spectrum of a 2% Cu‐doped sample are shown in Figure (c) and (d), respectively.…”
Section: Photodetection Properties Of Doped Zno 1d‐nssmentioning
confidence: 95%
See 4 more Smart Citations
“…The UV photodetectors used the multiple 1D‐NSs method. Figure (a) and (b) reveal the photocurrent spectra and UV on/off functional switching of the Cu‐doped ZnO and pure ZnO 1D‐NSs . The photocurrent spectra allow sufficient time to show the de‐trapping yield, and this and an X‐ray photoelectron spectroscopy (XPS) spectrum of a 2% Cu‐doped sample are shown in Figure (c) and (d), respectively.…”
Section: Photodetection Properties Of Doped Zno 1d‐nssmentioning
confidence: 95%
“…A higher photocurrent gain has been achieved by different methods, such as decreasing the dark current and increasing the photocurrent and absorption cross section of the material. S. Sarkar et al reported the growth of a ZnO seed layer on a glass substrate via a DC magnetron sputtering technique, and a 2% Cu‐doped ZnO nanorod array on a substrate via a hydrothermal method . The UV photodetectors used the multiple 1D‐NSs method.…”
Section: Photodetection Properties Of Doped Zno 1d‐nssmentioning
confidence: 99%
See 3 more Smart Citations